Resolution Influence on CRT Screen Picture Parameters Evaluation - Vaitkūnas, M.; Dosinas, A.; Bartkevičius, V. (Elektronika ir Elektrotechnika, 2004)
Some problems caused by the certain spectral and raster effects when colour test pattern is acquired from the CRT screen and decomposed into separate colour components are discussed. Acquisition of the test pattern is performed with colour video cameras. In the case of limited optical magnification more than one luminous phosphor spot are projected into one cell of the video camera sensor. Peculiarities of various methods of colour decomposition were estimated, by modelling video camera output signals and using different ratios of camera reading aperture and phosphor spot area. The results and recommendations are given. Ill. 4, bibl. 6 (in Lithuanian; summaries in Lithuanian, English and Russian.).